Divided Square Difference Cordial Labeling of Various Graphs - Vimal Patel; Suresh Sorathia; Amit Rokad (International Journal of Mathematics And its Applications, 2025)
In this paper we prove that alternate triangular belt graph, twig graph, duplication of the top vertex Alternate triangular snake graph, duplication of top vertex Pentagon snake graph, jellyfish (n,n), Spider graph with n spokes S_n,2 are divided square difference cordial graphs.